2000
DOI: 10.1002/(sici)1520-6300(200005/06)12:3<405::aid-ajhb11>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in relative leg length in post-war Japan

Abstract: Longitudinal secular changes of height and estimated leg length (ELL) or subischial leg length of Japanese boys and girls were investigated using data published in “The Statistical Report of the School Health Survey” of the Ministry of Education, Science, Sports and Culture, Japan. A significant trend towards greater relative leg length (long‐leggedness) among Japanese children and youth has occurred during the period of about four decades covered by this study. After showing a strikingly consistent trend at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…However, there was a dramatic difference between the two countries in that Japan showed virtually no change in timing after 1970, whereas in South Korea puberty occurred 6 months earlier in 2005 than in 1997. Ali et al (2000) also found that in Japan, age at peak height velocity plateaued after 1970.…”
Section: Resultsmentioning
confidence: 90%
“…However, there was a dramatic difference between the two countries in that Japan showed virtually no change in timing after 1970, whereas in South Korea puberty occurred 6 months earlier in 2005 than in 1997. Ali et al (2000) also found that in Japan, age at peak height velocity plateaued after 1970.…”
Section: Resultsmentioning
confidence: 90%
“…Extremities of stature proportions are different compared to those in the past owing to different lifestyles. Therefore, new stature estimation formulae are needed to reflect modern relative leg length [3,31]. There is a little difference between the formulae for stature estimation of Koreans and other populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have shown that North Koreans are shorter than South Koreans (see Schwekendiek and Pak 2009 for a metaanalysis), and researchers attribute these differences to nutrition. Similarly, height increased in the Japanese population in the generation born after World War II (Ali et al 2000). Height also tends to vary by socioeconomic status within countries; children from more well-off families are taller than children from poorer families (even in developed countries like the U.S.; Eveleth and Tanner 1990).…”
Section: What Else Affects Human Height?mentioning
confidence: 99%